Elementary School Teachers' Perspectives on Utilizing Artificial Intelligence for Developing Learning Media - Rachmadtullah, Reza; Mareyke Jessy Tanod, Mareyke Jessy Tanod; Rasmitadila., Rasmitadila; Irawan, Nico; McNeilly, Alan; Suharni, Suharni (Journal of Integrated Elementary Education, 2024)
The rapid advancement of Artificial Intelligence (AI) technology has brought about significant changes in education, particularly in elementary school settings. Integrating AI programs has led to substantial modifications, offering valuable support to educators in developing learning media. This study employed qualitative research to investigate elementary school teachers' viewpoints on utilizing AI for developing learning media, its integration into teaching activities, and the specific AI types utilized. The findings emphasized the crucial role of AI in education, highlighting the importance of careful AI deployment aligned with specific instructional needs and educational goals. Educators appreciated the significant assistance provided by AI in accessing a wide range of information and reference materials essential for creating engaging learning content. Additionally, participants noted the customized nature of their AI usage, tailored to their teaching requirements and desired educational outcomes. The research emphasized teachers' reliance on AI for information access and content development and underscored its vital role in creating a safe and enriching educational environment for educators and students.